Integration of Multi-Index Method and Qual2kw Evaluation Modeling of Quality Status and Pollutant Dispersion Pattern of Perian River in Kutai Kartanegara - Dwi Fitria Sari; Taufik Hamdani; Syelvialousiana Ningsih Kalauw; Rina Ermawati; Rudi Kartika; Slamet Ningsih Hadi Raharjo (Universitas Nusa Cendana, 2026)
This study is intended to assess water quality and determine the pollution status of the Perian River in its upstream (Perian Village) and downstream (Muara Aloh Village) sections in 2025. (COD) parameters. The findings reveal a marked deterioration in water quality from the upstream to the downstream segment of the river. Based on the CCME- WQI, both locations were categorized as